Community-Based Rehabilitation of Degraded Lands: Household Participation and Future Sustainability in West Harerge, Ethiopia - Midekso Rorisa; Mengist Mulatu; Shimeles Abebaw (Journal of Landscape Ecology)
Land degradation poses a critical threat to household livelihoods and environmental stability in Ethiopia, contributing to declining agricultural productivity and persistent food insecurity. Community-led rehabilitation of degraded lands, which are vital for local livelihoods, emerges as a timely solution to this pressing issue. This study evaluates the households decision on participation rehabilitation of degraded land and future sustainability in the Kunti watershed, West Harerge, Ethiopia. Data was collected from 197 households, categorized as 105 participant and 92 non-participant, alongside secondary sources including reports and literature. Findings reveal that rehabilitation efforts significantly improved local livelihoods by enhancing crop productivity, reducing soil erosion, increasing water availability, regulating rainfall, providing fodder, generating income from cattle fattening, and boosting biodiversity. A logit model analysis identified factors influencing household participation, such as family size, agricultural land size, and proximity to rehabilitation areas, with statistical significance below the 10 % level. To ensure sustainability, the study recommends clear land tenure and user rights, equitable benefit sharing, participatory forest management to foster ownership, greater women’s involvement in decision-making, and the development of small-scale enterprises within the rehabilitation sites.